Well posedness and stability result for a microtemperature full von Kármán beam with infinite‐memory and distributed delay terms. (28th February 2022) - Choucha, Abdelbaki; Ouchenane, Djamel
Abstract : This work is concerned with a full von Kármán beam in the presence of infinite‐memory, microtemperature, and distributed delay terms. First, we establish the well posedness of the system. Second, we considered the kernel h : ℝ + → ℝ + satisfying h ( t ) ≤ ξ ( t ) H ( h ( t ) ), ∀ t ∈ ℝ +, where ξ and H are functions satisfying some specific properties, and under this very general hypothesis on the behavior of h at infinity, we prove the stability of the system.